2015
DOI: 10.12968/bjsn.2015.10.6.280
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a school nurse intervention on adolescents' knowledge about healthy eating

Abstract: Background: The adolescent developmental stage has been described by researchers as a period in which decision-making abilities and independence skills are developed; therefore, this period may attract more attention from health-care providers as a key time for establishing healthy life styles and positive adaptive behaviours, such as nutritional behaviours. Methods: A quasi-experimental control group, and post-test only design was used. A school-based healthy nutrition educational programme was implemented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Nurses presented a four-session education program to all adolescents aged 12-15 years in their school. Increases in student nutrition knowledge were observed in the intervention group compared to the control group after the intervention, however no examination of nurse experiences in implementing the program were explored [24]. Hence, while similar research exists suggesting health promotion interventions with nurses are feasible and useful, we believe our study is the first to implement an eating disorder prevention program in a community-based nurse setting to promote healthful eating and positive body image with parents of preschool children.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nurses presented a four-session education program to all adolescents aged 12-15 years in their school. Increases in student nutrition knowledge were observed in the intervention group compared to the control group after the intervention, however no examination of nurse experiences in implementing the program were explored [24]. Hence, while similar research exists suggesting health promotion interventions with nurses are feasible and useful, we believe our study is the first to implement an eating disorder prevention program in a community-based nurse setting to promote healthful eating and positive body image with parents of preschool children.…”
Section: Discussionmentioning
confidence: 82%
“…A controlled trial by Pbert et al (2013), conducted with seven nurses delivering a six-session counselling intervention to assist larger-bodied adolescents with changes in eating and physical activity, found 75% of nurses could incorporate the intervention into their daily work and found it acceptable for the adolescents they worked with [23]. Similarly, Al-Yateem and colleagues (2015) conducted a quasi-experimental trial of an intervention implemented by school nurses to increase adolescents' knowledge of healthy eating [24]. Nurses presented a four-session education program to all adolescents aged 12-15 years in their school.…”
Section: Discussionmentioning
confidence: 99%
“… 9 This review identified several articles with a school-based intervention that reported a transfer of knowledge and behaviors into the home environment. 30 , 46 , 47 In addition, Başkale and Bahar 31 noted that after mothers were given nutrition education as a part of a school-wide intervention, their children’s health behaviors improved with “healthy food” consumption increasing further. It is important to note that not all children will have the independence to change their health behaviors in the home environment, 31 given their autonomy will be influenced by their SD.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity has been described by the World Health Organization (WHO, 2003(WHO, , 2014a as ''one of the most serious public health challenges of the 21st century,'' with the rates of obesity more than doubled among younger children and quadrupled in adolescents in the past 30 years (Center for Disease Control and Prevention, 2015). In the UAE and the region, rapid urbanization and changes in lifestyle have taken place, characterized by more consumption of processed and fast food and less physical activity particularly in school age (Al-Yateem et al, 2015;Ng et al, 2011). In repeated studies, the WHO (2003, 2014a) identified 74% of the Emirati population as overweight, with 37% being obese.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies report various health-care interventions targeting multiple health problems and issues facing schoolchildren. These include weight management strategies, managing chronic conditions such as asthma and diabetes, assessment and management of child abuse cases among others (Al-Yateem, Attia, AlYafei, Mohammed, & Mustafa, 2015; Drake, Stewart, Muggeo, & Ginsburg, 2015; Faro, Ingersoll, Fiore, & Ippolito, 2005; Hanson, Aleman, Hart, & Yawn, 2013; Kraft & Eriksson, 2015; Kubik & Lee, 2013; Mäenpää, Paavilainen, Åstedt-Kurki, & Åstedt-Kurki, 2013).…”
Section: Introductionmentioning
confidence: 99%